2022
DOI: 10.1177/10464964211069328
|View full text |Cite
|
Sign up to set email alerts
|

Use of Technology in the Study of Team-Interaction and Performance

Abstract: Direct observation of groups is labor-intensive. As a result, current research on small groups often relies on retrospective ratings. Recent developments in sensor-technology have eased data gathering, leading to a renewed interest in direct observation of groups. Sensor technology has potential, but also limitations; research has been technology- and data-driven with less recognition of the large body, and long history, of research and theory building. We review the literature on technology in small group res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…One possible reason for this trend of within-team homogeneity might be the studies’ exclusive reliance on interviews, surveys, and observations to collect data. These data collection methods mainly involve asking participants’ general perceptions in a retrospective manner or relying on one researcher’s overall observations around team behaviors (Sjøvold et al, 2022). Thus, the methods have limitations in capturing individual members’ moment-to-moment actions/interactions, as well as tracking processes of connecting numerous deviations in members’ actions/interactions to team performance (Sjøvold et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible reason for this trend of within-team homogeneity might be the studies’ exclusive reliance on interviews, surveys, and observations to collect data. These data collection methods mainly involve asking participants’ general perceptions in a retrospective manner or relying on one researcher’s overall observations around team behaviors (Sjøvold et al, 2022). Thus, the methods have limitations in capturing individual members’ moment-to-moment actions/interactions, as well as tracking processes of connecting numerous deviations in members’ actions/interactions to team performance (Sjøvold et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…These data collection methods mainly involve asking participants' general perceptions in a retrospective manner or relying on one researcher's overall observations around team behaviors (Sjøvold et al, 2022). Thus, the methods have limitations in capturing individual members' moment-tomoment actions/interactions, as well as tracking processes of connecting numerous deviations in members' actions/interactions to team performance (Sjøvold et al, 2022). Recent literature suggested that individuals in a team engage differently in and make sense of team processes (actions and interactions) and emergent states (Alshamsi et al, 2015(Alshamsi et al, , 2016van Knippenberg & Mell, 2016).…”
Section: Substantive Features Of the Reviewed Researchmentioning
confidence: 99%
See 1 more Smart Citation